Understanding the crystalline formation of triazene N-oxides and the role of halogen⋯π interactions. Issue 1 (6th December 2017) - Martins, Marcos A. P.; Salbego, Paulo R. S.; de Moraes, Guilherme A.; Bender, Caroline R.; Zambiazi, Priscilla J.; Orlando, Tainára; Pagliari, Anderson B.; Frizzo, Clarissa P.; Hörner, Manfredo
Abstract : Normalized parameters are presented to assist the interpretation of crystal mechanisms of a series of triazene N 1-oxides. The role of halogen⋯π interactions is discussed. Abstract : The crystallization of a series of 1-(4-halophenyl)-3-phenyltriazenide N 1-oxides (1–4 ) and 1-(phenyl)-3-phenyltriazenide N 1-oxide (5 ) was evaluated using the supramolecular cluster approach. This method is an efficient tool to assess the crystallization mechanism of compounds and, consequently, the steps involved in crystal formation. Compounds1 and4 show crystallization in two main steps while compounds2 and3 present three main steps, in which column formation occurs in the first step. The crystallization process for5 occurs in 3 main steps, starting from a robust dimer formation (−16.82 kcal mol −1 ). Two new parameters – N CG % (topological and energetic contribution percentage) and NG/NC (energetic parameter/topological parameter ratio) – assisted in the interpretation of crystal growth. Compounds1–4 showed N CG % = 50 in the first step while compound5 reached only 50% of the contribution in the second step. The differences in N CG % were attributed to strong hydrogen bonds in the non-halogenated compound. The dominant parameter in each step of the crystallization process was indicated by the NG/NC parameter. The crystallization mechanism in all compounds was initially driven by an energetic process followed by a topological process. The existence of X⋯π interactions was shown and was observed to be a consequence of a topological process and without any major contributions to crystal formation. Thermal analysis and UV-vis spectral data were also discussed regarding the properties of these compounds.